Aplikasi Metode Markerless Augmented Reality Untuk Media Informasi Universitas Harapan Medan (UNHAR) Berbasis Android - Salsabila, Cut Sarah; Faradillah, Yanty; Nurjamiyah, Nurjamiyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Universitas Harapan Medan is a private university consisting of four faculties. In introducing the campus, the most commonly used promotional media is through brochures, banners, because it is considered the cheapest and fastest promotional media. The weakness of the brochure media which usually only contains text and images has not been able to provide accurate information about the real picture of how the campus looks like along with all the facilities owned by the campus. Therefore, through this research, an AR-based technology will be added to campus promotional media in the form of brochures distributed to the general public. With AR technology, virtual world objects can be added as if they are in a real environment in 3-dimensional form. To add this AR technology and connect it with promotional media in the form of brochures, a marker is attached to the brochure so that through an Android smartphone device, we seem to be in a real environment in 3 dimensions. The purpose of this research is to develop an AR-based Faculty information media application to increase the effectiveness of Faculty introduction to prospective new students for Campus 1 and Campus 2 of Universitas Harapan Medan. The result of this research is that AR technology can be used as a solution to the problems faced by campuses in promoting their educational institutions so that advertisements displayed to readers are more interactive, dynamic and more real, because they are able to show the building and all the facilities in it as real and real in the form of 3D and video.